7(t-3)+7t=7(2t+4)-11

Simple and best practice solution for 7(t-3)+7t=7(2t+4)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(t-3)+7t=7(2t+4)-11 equation:


Simplifying
7(t + -3) + 7t = 7(2t + 4) + -11

Reorder the terms:
7(-3 + t) + 7t = 7(2t + 4) + -11
(-3 * 7 + t * 7) + 7t = 7(2t + 4) + -11
(-21 + 7t) + 7t = 7(2t + 4) + -11

Combine like terms: 7t + 7t = 14t
-21 + 14t = 7(2t + 4) + -11

Reorder the terms:
-21 + 14t = 7(4 + 2t) + -11
-21 + 14t = (4 * 7 + 2t * 7) + -11
-21 + 14t = (28 + 14t) + -11

Reorder the terms:
-21 + 14t = 28 + -11 + 14t

Combine like terms: 28 + -11 = 17
-21 + 14t = 17 + 14t

Add '-14t' to each side of the equation.
-21 + 14t + -14t = 17 + 14t + -14t

Combine like terms: 14t + -14t = 0
-21 + 0 = 17 + 14t + -14t
-21 = 17 + 14t + -14t

Combine like terms: 14t + -14t = 0
-21 = 17 + 0
-21 = 17

Solving
-21 = 17

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x+2+x=1+3x-19 | | (24/x^2-16)-(3/x-4)=(2/x+4) | | -1/5x-2=-20 | | w=5(3)+5 | | 34=-(8n-4)-5(6n-6) | | 1=10 | | -4(v-1)=16-2v | | 2-a-(-b)+c+(-a)-b-(-c)=0 | | 12*11-(15-9)/3-(9-6) | | 4x-3y=32 | | b+3/2b+(b+45)+(2b-90)+90=560 | | 3(x+4)-4=8 | | 4a+2=36-5 | | 12X11(15-9)/3-(9-6) | | -3.6-r=-(-6r+0.6) | | 8x^2-2xy+7y^2=8 | | 9(84)=9 | | -3c+7a+5+17b+2c+2c+b+(-7a)=0 | | 4(2x-7)+33=-5(x-5)+17x-28 | | -5(-2x+2)=-9x | | -7x-3y=-7 | | 6st+9t+10s-15= | | -32-7x=4(4x-8) | | -3.6-r=(-6r+0.6) | | 4+4x-x^2-x^3=0 | | 3x-15+x=180 | | -6-2(-9x-8)=-3 | | s=q+3/x | | .40c+4-.20c=-9 | | -23=-t | | b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 |

Equations solver categories